Global cooling and enhanced Eocene Asian mid-latitude interior aridity - J. X. Li (Nature Portfolio, 2018)
The role Tibetan Plateau uplift played in Asian inland aridification remains unclear due to a paucity of accurately dated records. Here, the authors present a continuous aeolian sequence for the period >51–39 Ma, analysis of which indicates that aridification was driven by global climatic forcing rather than uplift.